Climate change in the movie weathering with you-critical discourse analysis of environmental issues - Normalis Amzah,; Habibah Ismail,; Ng, Lay Shi (Penerbit Universiti Kebangsaan Malaysia, 2023)
Climate change is one of the integral problems that has been affecting people worldwide. A lot has been discussed in the academic field, and awareness about this matter has been raised in mainstream media, including the entertainment industry. Numerous studies have been conducted to explore the representation of climate change in movies. Unfortunately, insufficient attention has been given to examining the significance of language, specifically the linguistic patterns employed in the films. Therefore, this paper explores the linguistic patterns of climate change represented in a Japanese animation blockbuster, Weathering with You. The movie, as depicted in the title, addressed climate change in both implicit and explicit ways. Through Critical Discourse Analysis (CDA) underpinned by the Ecological Concern Framework, the study examines the layers of meaning in the language use of both Japanese and English. Comparing the source language, which is Japanese, with English will provide a multifaceted representation of climate change through language patterns. The CDA method enabled the analysis to explore linguistic features and provides an approach to incorporate language with social issues. The finding shows that throughout the movie, there are repetitions of the words 'rain', 'sunshine', 'sky' and 'weather'. Each of the words represents a certain discursive practice. There are three practices pinpointed in the movie. First, excessive rain is a disturbance to human life; second, the weather is beyond the control of human power; and third, humans are capable of mitigating climate change. These discursive presented different ideologies that are related to how humans perceive climate change and how it influences their actions toward the issue. Seeing how climate change becomes a central focus of an animated blockbuster, which is well received by audiences all around the world, rather than a topic discussed by global leaders, we argue that it has become a concern of global citizens as well. The findings exposed how global audiences subconsciously perceive climate change, and it would provide some input for environmentalists who are pursuing public environmental behavioural change.